Perinatal Outcomes of Late Preterm Premature Rupture of Membranes in Twin Compared with Singleton Pregnancies: A Retrospective Cohort Study - Moon, Hye Yeon; Kim, Ho Yeon; Choi, Eui-Kyung; Kim, Hai-Joong (Perinatology (Online), 2024)
Objective: Preterm births in the late preterm period comprise more than half of all preterm births. However, perinatal outcome evaluation between singleton and multiple pregnancies is limited. This study aimed to compare the perinatal outcomes of preterm pre-labor rupture of membranes (PPROM) between twin and singleton pregnancies at 34 weeks to 36 weeks and 6 days. Methods: This retrospective case-control study included women with preterm births at the Tertiary Hospital between July 2006 and December 2023. We analyzed and compared the maternal and neonatal characteristics, especially intertwined neonatal morbidity and mortality, with those of singletons. Results: There were 52 twin and 317 singleton pregnancies. Women with twin pregnancies had shorter median latencies and fewer cases of histological chorioamnionitis than those with singleton pregnancies. Compared to the ruptured sac babies of twins and singletons, unruptured sac babies of twins had longer hospital stays and were more likely to require respiratory support and resuscitation immediately after delivery. Conclusion: Maternal outcomes of twins and singletons after PPROM differed in latency and histologic chorioamnionitis, whereas neonatal outcomes demonstrated more acute respiratory problems and longer hospital stays in twin babies with unruptured sacs. More cautious respiratory care is needed for infants with an unruptured sac immediately after birth. KCI Citation Count: 0